A influência do ambiente de trabalho na gestão do conhecimento de um estaleiro público - Palma, Marcos André Westphalen (2007)
This Master in Science dissertation was developed in the Knowledge Management (KM) and tries to prove the hypothesis that on a certain governmental institution the workers grade of motivation is relevant to achieve the productivity gain when the tools and techniques of Knowledge Management are used as it s expected on the specialized library. The case study analyses both the institution knowledge problems and the knowledge management tools and techniques that are used nowadays to solve them. The Shipyard´s Project Department answered questionnaires in which is shown the group chiefs perception on knowledge management and on its civil workers and outsourcing employees motivation. At the end, there s a couple of suggestions: to acquire new Knowledge Management tools and to implant new strategies to improve the worker s motivation, having as an objective to create synergy for a good shipyard´s performance so it can improve its action and social return.